The moderating role of credit growth limit: Differential impacts on real estate and non-real estate firms in Vietnam - Pham Duy , Tinh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study compares the moderating effect of Vietnam’s credit growth limit policy on the nonlinear relationship between bank credit and firm performance during the 2004‒2023 period, differentiating between real estate and non-real estate firms. Using panel data along with static and dynamic models, the study confirms an inverted U-shaped nonlinear relationship between bank credit and firm performance, indicating that excessive credit can be detrimental. The results indicate that real estate firms are more negatively sensitive (experiencing a sharper decline in performance) to high credit levels compared to other firms. More importantly, the credit growth limit policy has a positive moderating effect, mitigating the decline in performance when credit levels are high and flattening the inverted U-shaped curve. Notably, this positive effect is significantly stronger for the real estate firm group.